Selection of X chromosome of buffaloes sperm with Percoll gradients - Mota, A. V. [UNESP]; Oba, E. [UNESP]; Castro, A. [UNESP]; Araujo, G. H.M. [UNESP]; Stella, E. [UNESP]; Ramos, A. A. [UNESP] (Taylor & Francis, 2007)
The aim of the present study was to evaluate the selection of X chromosome of buffaloes sperm with Percoll gradients. The stock solution of Percoll was prepared in the proportion of 1:11 (1 part of Percoll:11 parts of a solution containing KCl 1M, NaH2PO4 0.1M, NaCl 1.5M and sodium HEPES 23.8 g/ml). In order to prepare 9 different gradients were added to the stocked Percoll the A solution (glicine-yolk extender) in the following proportions: 90, 80, 72, 65, 57, 49, 34 and 25%. A sample of 0.7 ml of the fresh semen was deposited at 2 ml of Percoll 80% for the sperm wash. The precipitate was put in tube with 0.7 ml of each gradient. Then, the precipitated was washed in TES solution by centrifugation (500xg for 10 minutes), and collected again and diluted in TES solution to be freeze. The presence of the F body in the spermatozoa was observed in 58.7 ± 5.4% of the control group and in 41.2 ± 5.4% of the treated group (p<0.01). This result showed an increment of 17.55 of male sperm in the Percoll's group. The reduction of the centrifugation force did not improve the percentage of X sperm.
Keywords: Buffaloes; Percoll gradients; Sperm; X chromosome